Effect of oxytocin administration on nerve recovery in the rat sciatic nerve damage model. Issue 1 (December 2015) - Gümüs, Bilal; Kuyucu, Ersin; Erbas, Oytun; Kazimoglu, Cemal; Oltulu, Fatih; Bora, Osman
Abstract Background Growth factors such as nerve growth factor (NGF) and insulin-like growth factor-1 (IGF-1) have been shown to play a role in the healing process of nerve injury. Recent researches have also shown that oxytocin administration activates these growth factors of importance for the healing of nerve tissue. The objective of the present study was to evaluate the effects of oxytocin on peripheral nerve regeneration in rats. Methods Twenty-four male Sprague-Dawley rats were underwent transection damage model on the right sciatic nerve and defective damage model on the left sciatic nerve. The animals were assigned to one of two groups: control group or treatment group (received 80 mg/kg oxytocin intraperitoneally for 12 weeks). The sciatic nerve was examined, both functionally (on the basis of climbing platform test) and histologically (on the basis of axon count), 3, 6, 9, and 12 weeks after the injury. Also, stereomicroscopic and electrophysiological evaluations were carried out. Results Significantly greater improvements in electrophysiological recordings and improved functional outcome measures were presented in the treatment group at 12-week follow-up. Stereomicroscopic examinations disclosed prominent increases in vascularization on proximal cut edges in the oxytocin group in comparison with the control group. Higher axon counts were also found in this group. Conclusion Intraperitoneal oxytocin administration resulted in accelerated functional, histological, and electrophysiological recovery after different sciatic injury models in rats.